The Faith Problem in James 2 - Chia, Philip Suciadi (Theological Journal Kerugma, 2024)
Faith is the main theme in James chapter two. Again, James has his exhortation and reason (purpose) to back up his exhortation. In this chapter, however, James uses a personal (2:4, 6), theological (2:5, 7, 19-20), and scriptural reflection (2:8-11, 21, 23, 25) in his reason (purpose). These reflections reveal that James exhorts his readers that are familiar with a Jewish background and his exhortation is personal. Interestingly, James provides his commentaries on Biblical quotations (2:22, 24, 26).